Differences abnormal return and cumulative abnormal return financial sector issuers for the previous period and time of the covid-19 pandemic - Puput Rahmah Romdiani -; Gatot Iwan Kurniawan (Financial Management Studies, 2021)
The existence of the covid-19 virus impacts several economic sectors in Indonesia so that it affects the investment climate, which has also decreased. This research was conducted to prove the occurrence of market reactions with the virus through differences in abnormal returns and Cumulative Abnormal Returns of financial sector issuers before and during the Covid-19 pandemic. The population in this study were companies included in the financial sector issuers for January 2019 - April 2020, which consisted of 51 companies; the sample selection used a purposive sampling technique so that the sample of this study became 11 companies. The method used is the descriptive comparative method through the Paired Sample T-Test. The results showed significant differences in the Abnormal Returns of Financial Sector Issuers in the Pre-Covid-19 Pandemic Period. As for the Cumulative Abnormal Return variable for Issuers in the financial sector, there is no difference between before and the Covid-19 Pandemic Period.